Droplet impact on superheated surfaces - Khavari, Mohammad (2017)
The impact of droplets on heated substrates is a crucial process in a diverse range of technological and industrial applications such as thermal spray, electronics cooling and material processing. Of particular importance is the situation in which the substrate is heated above the liquid boiling point. In such case, hydrodynamic behaviors of the impacting droplets, such as spreading and possible splashing, are accompanied by boiling processes, such as liquid-vapor phase transition, bubble generation, and droplet ejection. These intangible physical processes make it challenging to understand and control quantities of practical interests such as the heat transfer rate from the surface to the liquid. In a typical boiling process, the liquid absorbs heat from the surface, vaporizes, and the generated vapor is carried away by natural convection. The heat flux remains increasing with temperature as long as the liquid maintains contact with the surface; it drops abruptly when excessive vapor completely covers the surface. The former case is commonly referred to as the contact boiling regime, while the latter one is known as the Leidenfrost regime. The transition to the Leidenfrost regime therefore is directly linked to the upper limit of boiling heat transfer. Current theories of the Leidenfrost transition assume a priori existence of the vapor layer, thus focusing on its hydrodynamics without making reference to the contact boiling regime. The main aim of this research is to obtain a physical understanding of the Leidenfrost transition. To this end, we systematically study the boiling phenomena of droplet impinging on superheated substrates made of materials having low and high thermal conductivities, namely glass and sapphire. The difference in thermal conductivity of impacted substrates results in distinct boiling behaviors of the liquids: we observe new regimes, i.e., fingering boiling and oscillating boiling regimes for substrate of low and high thermal conductivities, respectively. In particular, detailed observation and analysis of the oscillating boiling regime allows us to elucidate a new mechanism of the Leidenfrost transition based on competition between two effects: separation of liquid from the heated surface due to localized boiling, and rewetting. We show that the predicted values of the Leidenfrost temperature are consistent with the experimentally measured ones for various liquids having widely different properties, suggesting that complex entanglement between the involving hydrodynamic and thermodynamic processes of the Leidenfrost phenomenon can be understood under the newly proposed mechanism. Our findings offer a new theoretical framework to treat the Leidenfrost transition, a crucial step towards complete control of the Leidenfrost phenomenon.